Gaya Komunikasi Trainer Sekolah Mengemudi Dalam Proses Belajar Mengemudi Siswa VIP Driving School Padang - Rahayu, Fajria Ika; Flowerina, Indria (CV. ITTC INDONESIA, 2024)
Communication style is a way that is shown by someone in the process of conveying messages and using the correct language style. This style can be in the form of words or called verbal or non-verbal such as gestures, body language, and roles in the use of space, time and distance. The style of communication used by the VIP driving school trainer during the driving course makes the student understand the material conveyed by the trainer during the learning process. Course service users are accompanied and trained by trainers during driving courses. This is a learning guidance related to driving skills which aims to provide driving course students with knowledge of how to drive a car. This research method uses qualitative research methods and uses Adaptation Interaction theory. This theory was developed by Judee Burgoon, Lesa Stren, and Leesa Dillman in 1995. The results of this study are the communication style of VIP driving school driving course trainers who use effective communication during the driving learning process. going on. What makes driving course students easy to understand the material provided by the trainer. And there are several kinds of communication styles that are used as long as the trainer teaches students to drive.